Effect of Allowable Vertical Load and Length/Diameter Ratio (L/D) on Behavior of Pile Group Subjected to Torsion (Journal of Engineering, 2014)
Some structures such as tall buildings, offshore platforms, and bridge bents are subjected to lateral loads of considerable magnitude due to wind and wave actions, ship impacts, or high-speed vehicles. Significant torsional forces can be transferred to the foundation piles by virtue of eccentric lateral loading. The testing program of this study includes one group consists of 3 piles, four percentages of allowable vertical load were used (0%, 25%, 50%, and 100%) with two L/D ratios 20 and 30, vertical allowable load 110 N for L/D = 20 and 156 N for L/D = 30. The results obtained indicate that the torsional capacity for pile group increases with increasing the percentage of allowable vertical load, when the percentage of allowable vertical load was 100% and L/D ratio (20) the torsional capacity for pile group increases about 42% if compared with the torsional capacity when the percentage of allowable vertical load was 0% for the same L/D ratio. Also increasing L/D ratio leads to increasing the torsional capacity of pile group, when the percentage of allowable vertical load is 100% and L/D ratio (30), the torsional capacity for pile group increased about 51% if compared with torsional capacity when L/D ratio was (20) for the same groups and the same percentage of allowable vertical load. At failure the twist angle for pile group remain constant 3° when the percentage of allowable load change from 0% to 100 and L/D ratio 20, while it decreases from 2.9° to 2.7° when the percentage of allowable load change from 0% to 100% respectively and L/D ratio 30.